Thursday

March 5, 2015

March 5, 2015

Posted by **don** on Wednesday, September 26, 2012 at 3:43pm.

- Math -
**Steve**, Wednesday, September 26, 2012 at 3:55pmf(-x) = -f(x)

x = g(y)

-x = g(-y) but -x = -(g(y)) = -g(y)

so, g is odd

**Answer this Question**

**Related Questions**

Calculus, check my answers, please! 3 - Did I get these practice questions right...

Math - Let f and g be two odd functions. Prove that: a) f + g is an odd function...

odd and even functions - Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x...

discrete math - use a direct proof to show that the product of two odd numbers ...

discrete math - prove that if n is an integer and 3n+2 is even, then n is even ...

college algebra - Let f denote an odd function and g an odd function. Decide ...

Maths - The first odd number can be expressed as 1 = 1squared - 0squared. The ...

Calculus, check my answers, please? :) - Okay, so I think these are right, but I...

math - I know It's probably an easy question but I don't know remember how to do...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...